Saccharomyces cerevisiae – Insects Association: Impacts, Biogeography, and Extent - Meriggi, Niccolo’; Di Paola, Monica; Cavalieri, Duccio; Stefanini, Irene (Frontiers in Microbiology, 2020)
Over the last few years, an increasing number of studies have reported the existence of an association between the budding yeast Saccharomyces cerevisiae and insects. The discovery of this relationship has called into question the hypothesis that S. cerevisiae is unable to survive in nature and that the presence of S. cerevisiae strains in natural specimens is the result of contamination from human-related environments. S. cerevisiae cells benefit from this association as they find in the insect intestine a shelter, but also a place where they can reproduce themselves through mating, the latter being an event otherwise rarely observed in natural environments. On the other hand, insects also take advantage in hosting S. cerevisiae as they rely on yeasts as nutriment to properly develop, to localize suitable food, and to enhance their immune system. Despite the relevance of this relationship on both yeast and insect ecology, we are still far from completely appreciating its extent and effects. It has been shown that other yeasts are able to colonize only one or a few insect species. Is it the same for S. cerevisiae cells or is this yeast able to associate with any insect? Similarly, is this association geographically or topographically limited in areas characterized by specific physical features? With this review, we recapitulate the nature of the S. cerevisiae-insect association, disclose its extent in terms of geographical distribution and species involved, and present YeastFinder, a cured online database providing a collection of information on this topic.